2019
DOI: 10.1097/mpa.0000000000001405
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effect of Patient Characteristics, Geographical Utilization, and Patient Outcomes for Total Pancreatectomy Alone and Total Pancreatectomy With Islet Autotransplantation in Patients With Pancreatitis in the United States

Abstract: Objectives A selective therapy for pancreatitis is total pancreatectomy and islet autotransplantation. Outcomes and geographical variability of patients who had total pancreatectomy (TP) alone or total pancreatectomy with islet autotransplantation (TPIAT) were assessed. Methods Data were obtained from the Healthcare Cost and Utilization Project National Inpatient Sample database. Weighed univariate and multivariate analyses were performed to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Prior studies have shown that race is an independent predictor of a late diagnosis of PC and poor survival in all stages (20)(21)(22)(23)(24). In these studies, the survival differences by race were driven largely by differences in surgery and treatment rates in early stage or potentially curative disease settings (3,4,12,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that race is an independent predictor of a late diagnosis of PC and poor survival in all stages (20)(21)(22)(23)(24). In these studies, the survival differences by race were driven largely by differences in surgery and treatment rates in early stage or potentially curative disease settings (3,4,12,25).…”
Section: Discussionmentioning
confidence: 99%
“…Hispanics have a heterogeneous ancestry, including Indigenous, Caucasian, and African ancestry. Since other studies have evaluated this ethnic group (24,29), we chose to focus on the differences between Black vs. White patients irrespective of ethnicity, as we believe this would partially eliminate biases from heterogeneous ancestry. We acknowledge this is not the generally accepted standard evaluation of race/ethnicity and that even black ancestry has significant heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing these advantages, the majority of commercial insurance carriers in the United States and in several European countries should consider reimbursing IAT. Hopefully, the multicenter TPIAT study, which is currently underway, will provide further evidence to change the position of the remaining insurance carriers (notably the Centers for Medicare and Medicaid Services) and clinicians who have not yet recognized the benefits of IAT [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our own group has provided autologous islets for 152 TPAITs since 2007, including 26 juvenile patients (under 18 years of age) as young as 7 years [9]. The trend towards TP and TPAIT can be observed in all geographical areas of the US [15]. Improvements to the procedure have resulted in better outcomes over time [16].…”
Section: Autologous Islet Txmentioning
confidence: 99%